Nonanthropomorphic exoskeleton with legs based on eight-bar linkages. (19th February 2018) - Godoy, Jorge Curiel; Campos, Ignacio Juárez; Pérez, Lucia Márquez; Muñoz, Leonardo Romero
This article presents the principles upon which a new nonanthropomorphic biped exoskeleton was designed, whose legs are based on an eight-bar mechanism. The main function of the exoskeleton is to assist people who have difficulty walking. Every leg is based on the planar Peaucellier–Lipkin mechanism, which is a one degree of freedom linkage. To be used as a robotic leg, the Peaucellier–Lipkin mechanism was modified by including two more degrees of freedom, as well as by the addition of a mechanical system based on toothed pulleys and timing belts that provides balance and stability to the user. The use of the Peaucellier–Lipkin mechanism, its transformation from one to three degrees of freedom, and the incorporation of the stability system are the main innovations and contributions of this novel nonanthropomorphic exoskeleton. Its mobility and performance are also presented herein, through forward and inverse kinematics, together with its application in carrying out the translation movement of the robotic foot along paths with the imposition of motion laws based on polynomial functions of time.